INFLUÊNCIA DA ATIVIDADE FÍSICA NA QUALIDADE DE VIDA E SAÚDE MENTAL DE IDOSOS DE UM MUNICÍPIO DO OESTE CATARINENSE - Dagostini, Carmen Lucia Figueiredo; Pletsch Benetti, Maylaine Carina (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
The research is a research project that seeks to collect theoretical data about aging and the influence of physical activity on quality of life and mental health in old age. m as an objective to verify the quality of life in elderly practitioners and non-practitioners of physical activity in a city in the Midwest of Santa Catarina and the influence of these activities on their daily lives, both in prevention and in the promotion of mental health. The study is characterized as exploratory and quantitative in nature. The sample is composed of 40 elderly people of both sexes, who were interested in participating in the research. For data collection, a semi-structured questionnaire with closed questions and use of the QSG - Goldberg General Health Questionnaire was used. Data analysis revealed that most elderly people classify physical exercise as an important factor for their health and that regular physical activity positively influences the elderly's quality of life and mental health, allowing greater resourcefulness. in other daily activities, it may also be a factor that delays common psychopathologies in aging. The theoretical data and the results of the data analysis allowed us to describe the aging process in a broad way, elucidating the importance of regular physical activity for the mental health of the elderly person, since the more active a person is, the less physical limitations and psychics she presents.